YURISPRUDENSI SEBAGAI SUMBER PEMBARUAN HUKUM DALAM SISTEM CIVIL LAW INDONESIA: KAJIAN PUSTAKA ATAS FUNGSI PENEMUAN HUKUM OLEH HAKIM - Gunawan Widjaja; Cecep Suhardiman (JOURNAL OF LAW AND NATION, 2025)
This study discusses the role of jurisprudence as a source of legal reform in Indonesia's civil law system by examining the function of judicial discovery through a literature review. In practice, the limitations of written regulations often encourage judges to interpret and form new norms to fill gaps and adapt the law to societal developments. The process of legal discovery (rechtsvinding) produces decisions that not only resolve individual cases but also form jurisprudence that serves as a guideline for resolving similar cases in the future. This study emphasises that jurisprudence plays a significant role as a driver of national legal reform, although it remains within the framework and supremacy of legislation. Therefore, synergy between judicial discovery and formal legislation is essential to achieve an adaptive, responsive, and just legal system in Indonesia.